Peran Guru Dalam Mengembangkan Bakat Siswa Di Sekolah Dasar Negeri 34/I Teratai - Utomo, Agung; Kurniawan, Agung Rimba; Chan, Faizal; Juliani, Tania; Riski, Rosi Dwi; Ismaini, Erni (Jurnal PGSD, 2019)
The purpose of this study is to describe the role of teachers in developing student talent in  Teratai 34/I Primary Schools. This study uses a qualitative approach to the type of phenomenological approach that is intended to describe a phenomenon experienced by the object of the researcher. The subjects in this study involved class teachers and students. Then, the research data were collected by observation and interview techniques, and supported by documentation. The conclusion of the research that has been done is that teachers at SDN 34 / I Lotus develop students' talents in both the academic and non-academic fields. Various attempts were made by teachers such as supporting by giving free time for additional learning in the academic field, as well as bringing in outside trainers for non-academic activities such as drum bands, karate, and scouts.